2014
DOI: 10.1093/pcp/pcu163
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Cytosolic Acyl-CoA-Binding Proteins Play Combinatory Roles in Pollen Development

Abstract: In Arabidopsis, six acyl-CoA-binding proteins (ACBPs) have been identified and they have been demonstrated to function in plant stress responses and development. Three of these AtACBPs (AtACBP4-AtACBP6) are cytosolic proteins and all are expressed in floral organs as well as in other tissues. The roles of cytosolic AtACBPs in floral development were addressed in this study. To this end, a T-DNA insertional knockout mutant of acbp5 was characterized before use in crosses with the already available acbp4 and acb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 66 publications
2
55
0
Order By: Relevance
“…Subsequent GUS assays revealed the expression of AtACBP4 in pollen grains, AtACBP5 in microspores and tapetal cells, and AtACBP6 in pollen grains, microspores and tapetal cells, suggesting their overlapping roles in pollen development [122]. In addition, AtACBP6 was also expressed in the cotyledons, hypocotyl and cotyledonary-staged embryo in GUS-histochemical assays [32].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequent GUS assays revealed the expression of AtACBP4 in pollen grains, AtACBP5 in microspores and tapetal cells, and AtACBP6 in pollen grains, microspores and tapetal cells, suggesting their overlapping roles in pollen development [122]. In addition, AtACBP6 was also expressed in the cotyledons, hypocotyl and cotyledonary-staged embryo in GUS-histochemical assays [32].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…2) [28]. Recent expression profiles by quantitative RT-PCR showed that AtACBP4 to AtACBP6 were highly expressed in the inflorescences [122].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For histochemical examination, the specimens were embedded and sectioned in Technovit 7100 (Electron Microscopy Sciences). Sections were stained with the periodic acid-Schiff's reaction for total insoluble carbohydrates and Amido Black 10B for protein and then imaged with a Leitz photomicroscope using a Nikon DS-Fi2 digital camera according to Hsiao et al (2015).…”
Section: Light Microscopymentioning
confidence: 99%
“…Mutant acbp4/5/6 pollen grains exhibit defects in oil bodies and the outer pollen cell wall. [50] Hence, LACS and ACBPs work in a combination to export the lipid precursors for cell wall deposition.…”
Section: Lacss Export Lipid Precursors Out Of the Ermentioning
confidence: 99%